2020
DOI: 10.2147/jpr.s275254
|View full text |Cite
|
Sign up to set email alerts
|

<p>Selective Ablation of Descending Serotonin from the Rostral Ventromedial Medulla Unmasks Its Pro-Nociceptive Role in Chemotherapy-Induced Painful Neuropathy</p>

Abstract: Purpose: Chemotherapy-induced painful neuropathy (CIPN) is a severe adverse effect of many anti-neoplastic drugs that is difficult to manage. Serotonin (5-hydroxytryptamine, 5-HT) is an important neurotransmitter in the rostral ventromedial medulla (RVM), which modulates descending spinal nociceptive transmission. However, the influence of the descending 5-HT from the RVM on CIPN is poorly understood. We investigated the role of 5-HT released from descending RVM neurons in a paclitaxel-induced CIPN rat model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In neuropathic or inflammatory pain states, blocking the 5-HT3R specifically attenuates 5-HT pronociceptive actions in the RVM while activation of the 5-HT3R plays a facilitatory role in nociceptive responses. These findings were in parallel with the observations that a descending release of 5-HT from the RVM combined with the upregulation of 5-HT3R expression in spinal cord neurons was detected after inflammation and nerve injury ( Wei et al, 2010 ; Wang et al, 2019 ; Liu et al, 2020 ). Thus, it is confirmed that spinal 5-HT3R mainly mediates descending facilitation under abnormal pain conditions.…”
Section: Neural Circuits and Neurotransmitters Modulating Projections...supporting
confidence: 87%
See 1 more Smart Citation
“…In neuropathic or inflammatory pain states, blocking the 5-HT3R specifically attenuates 5-HT pronociceptive actions in the RVM while activation of the 5-HT3R plays a facilitatory role in nociceptive responses. These findings were in parallel with the observations that a descending release of 5-HT from the RVM combined with the upregulation of 5-HT3R expression in spinal cord neurons was detected after inflammation and nerve injury ( Wei et al, 2010 ; Wang et al, 2019 ; Liu et al, 2020 ). Thus, it is confirmed that spinal 5-HT3R mainly mediates descending facilitation under abnormal pain conditions.…”
Section: Neural Circuits and Neurotransmitters Modulating Projections...supporting
confidence: 87%
“…Thus, it is confirmed that spinal 5-HT3R mainly mediates descending facilitation under abnormal pain conditions. Specifically, activation of the p38 mitogen-induced protein kinase (p38MAPK) pathway in the RVM increases the expression of tryptophan hydroxylase (Tph), resulting in increased activities of ON cells and expression of 5-HT along with the silencing of OFF cells, which then act on the spinal 5-HT3R to activate ATP-gated P2X7 receptors in the microglia, and ultimately exerting pain hypersensitivity ( Liu et al, 2020 ). As 5-HT3R is also expressed on inhibitory GABAergic interneurons, antinociceptive effects are confirmed to correspond to activation of OFF cells in subcutaneously excited RVM 5-HT3R and GABA release in the GABA spinal cord in acute pain models ( Nasirinezhad et al, 2016 ; Kort et al, 2022 ).…”
Section: Neural Circuits and Neurotransmitters Modulating Projections...mentioning
confidence: 99%
“…Emerging mechanism in neuroscience research were evaluated namely in what concerns the gut-brain axis (78,91) or circadian regulation (53).…”
Section: Cannabinoidsmentioning
confidence: 99%
“…Intrathecal catheterization was performed as described previously [16,17]. Brie y, rats were anesthetized, a longitudinal 1.5 cm incision was made in the skin at the level of L4-L5, and the sphenoid of L4 was excised until the spinal dura was exposed.…”
Section: Preparation Of Cells and Modeling Of Bcpmentioning
confidence: 99%